2003
DOI: 10.1002/ab.10027
|View full text |Cite
|
Sign up to set email alerts
|

Staff survey results and characteristics that predict assault and injury to personnel working in mental health facilities

Abstract: The purpose of this study was to complete a mental health staff opinion survey to identify patient and staff characteristics associated with staff assault and injury in psychiatric treatment settings and to develop a model of prediction for staff assault and injury utilizing these survey variables. The data consisted of opinion surveys sent to staff of 15 child, adolescent, and adult psychiatry inpatient units in the United States. Multivariate logistic regression was used to determine the level of assault and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…In a study by Carmel and Hunter [1989], male nursing staff were almost twice as likely as female staff to be injured and nearly three times as likely to receive containment-related injuries. In contrast, in two other studies no differences were found between male and female nurses and their assault rate [Whittington, 1994;Cunningham et al, 2003]. …”
Section: Staff Variables and The Occurrence Of Aggressionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a study by Carmel and Hunter [1989], male nursing staff were almost twice as likely as female staff to be injured and nearly three times as likely to receive containment-related injuries. In contrast, in two other studies no differences were found between male and female nurses and their assault rate [Whittington, 1994;Cunningham et al, 2003]. …”
Section: Staff Variables and The Occurrence Of Aggressionmentioning
confidence: 63%
“…The impact of education was considered, and a low level of qualification was found to be associated with higher rates of assault [Whittington and Wykes, 1994;Cunningham et al, 2003]. In several studies it was found that the more inexperienced the staff were, the more they were exposed to assaults [Hodgkinson et al, 1985;Cunningham et al, 2003].…”
Section: Staff Variables and The Occurrence Of Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Carmel and Hunter (1989), male nursing staff were almost twice as likely as female staff to be injured and nearly three times as likely to receive containment-related injuries. In contrast, in two other studies, no differences were found between male and female nurses and their assault rate (Cunningham, Connor, Miller, & Melloni, 2003;Whittington, 1994). In several studies, it was found that more inexperienced staff were more likely to be exposed to assaults (Cunningham et al, 2003;Hodgkinson, Mcivor, & Philips, 1985;Whittington, Shuttleworth, & Hill, 1996).…”
Section: Determinants Of Aggressionmentioning
confidence: 84%
“…In contrast, in two other studies, no differences were found between male and female nurses and their assault rate (Cunningham, Connor, Miller, & Melloni, 2003;Whittington, 1994). In several studies, it was found that more inexperienced staff were more likely to be exposed to assaults (Cunningham et al, 2003;Hodgkinson, Mcivor, & Philips, 1985;Whittington, Shuttleworth, & Hill, 1996). Studies on the relationship between time of day and increase in aggression show that most incidents take place in the daytime, followed by the evening, and with the lowest rate found during the night.…”
Section: Determinants Of Aggressionmentioning
confidence: 84%